Numerical investigation of 660 MW pulverized coal-fired supercritical power plant retrofitted to oxy-coal combustion - Yadav S.; Mondal S.S. (My University, 2025)
A detailed investigation of the oxy-fuel combustion-based CCS consisting of air separation unit (ASU), supercritical boiler parameters and CO2 compression and purification unit (CPU) has been performed. A 660 MW supercritical power plant retrofitted to oxy-coal combustion has been simulated and analysed to investigate the operational characteristics of the oxy-coal combustion process by employing the process simulation tool Aspen plus. Moreover, the effect of important design parameters such as oxygen concentration of the oxidant, recycle ratio and purity of oxygen produced by ASU on the composition of flue gas, auxiliary power consumptions, CO2 recovery rate, CO2 product purity, and specific energy consumptions of O2 and CO2 has also been studied. The comparison of simulation results of the oxy-coal combustion and conventional air-fired combustion atmosphere has been presented. The excellent performance of oxy-coal combustion power plant has been observed in term of its ability to capture carbon dioxide with 95 % purity and 96 % recovery rate. The net efficiency of oxy-coal combustion power plant reduces by 10.4 % compared to the convention air-fired power plant. © 2020 Elsevier Ltd